Measuring the legal protection of academic freedom: The scorecard for South Africa - Beiter, K. D.; Karran, T. (South African Journal of Higher Education, 2025)
This article measures to what extent academic freedom as construed in terms of international human rights law, specifically UNESCO’s Recommendation on the Status of Higher-Education Teaching Personnel of 1997, is protected in South African law. It determines the elements of this right, operationalises these by way of 37 human rights-based indicators, and then assesses whether South Africa’s legal framework related to higher education and research adequately protects academic freedom and its structural safeguards, such as institutional autonomy, academic self-governance, and employment security, including tenure. The authors had previously applied this scorecard to determine the strength of the protection of academic freedom in the law of European countries. The analysis for South Africa shows that, as in Europe (and, as it were, most countries of the global North), rather than politically motivated “ideological” attacks, it is the utilitarian, economistic, and, in this sense, illiberal vision of higher education and research, reflected in law and in practice, that puts academic freedom under pressure in South Africa. As in European and in many other countries, market liberalism erodes academic freedom in South Africa, but, additionally, “transformationism” as well as the notion that universities should be development-oriented threaten academic freedom here. Remedying the situation, apart from legislative reform, will require reasserting the truth-seeking (and communicating) role of the university.